Processing method of artificial graphite secondary oversize product

By mixing the secondary sieve with artificial graphite semi-finished products, graphitization and carbonization treatment, and mixing it with modified asphalt, the problem of low utilization efficiency of secondary sieve is solved, the electrochemical performance is improved, and the battery material that efficiently utilizes the secondary sieve is achieved.

CN119637865AActive Publication Date: 2025-03-18FUJIAN SHANSHAN TECH CO LTD

Patent Information

Application Number
CN202411942014.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-18
Estimated Expiration
2044-12-26

AI Technical Summary

Technical Problem

The use efficiency of the secondary screens completed by artificial graphite is low, and simple dispersion and grading cannot be carried out, making it difficult to use as a normal battery material.

Method used

By mixing the broken-out and graded secondary screen with the normally produced artificial graphite semi-finished product, graphitization and high-temperature carbonization treatment, further mixing with modified asphalt, and processing the finished product, we obtain artificial graphite negative electrode material that meets the requirements.

Benefits of technology

The electrochemical properties of the material are improved, such as specific surface area, tap density and powder compaction density, and the effective utilization of the materials on the secondary screen is achieved, and is suitable for battery products with high capacity requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119637865A_ABST
    Figure CN119637865A_ABST
Patent Text Reader

Abstract

The invention discloses a treatment method of artificial graphite secondary oversize products. The treatment method comprises the following steps: (1) sequentially carrying out scattering treatment and grading treatment on the artificial graphite secondary oversize products to obtain a material A; (2) mixing the material A with an artificial graphite semi-finished product, and graphitizing to obtain a material B; (3) mixing the material B with modified asphalt, and carbonizing to obtain a material C; and (4) carrying out finished product processing treatment on the material C to obtain the treated artificial graphite negative electrode material, according to the treatment method, the scattered and graded material is further mixed with a normally produced artificial graphite semi-finished product, and then graphitization and high-temperature carbonization are carried out, so that the electrochemical performance of the material, such as the specific surface area, the tap density and the powder compaction density, is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of battery materials, in particular to a method for processing artificial graphite secondary screen material. Background Art

[0002] In the process of artificial graphite processing, some unqualified materials will inevitably appear. The most regrettable one is the screened material after processing. In terms of performance, it has a discharge capacity close to that of the finished product, but its particle size is too large and the morphology is irregular, which has a negative impact on the consistency of the battery when making batteries. The first screened material of artificial graphite is generally subjected to some simple physical treatment, such as shaping, screening, etc., and then mixed with normal materials in a small proportion for shipment, but the second screened material has a larger particle size and cannot be simply broken up and reused. Therefore, it is necessary to develop a method to process the second screened material of artificial graphite to meet the normal product shipment requirements.

[0003] CN115814921A discloses a method for processing artificial graphite oversize, wherein the oversize of the sieved artificial graphite material is transported to the storage bin of a rod pin grinder and disperser, and the disperser is used for dispersion, wherein the main machine frequency of the disperser is 20-100Hz, the rotation speed is 1000-3000r / min, the feeding frequency is 3-18Hz, and the dispersion efficiency is 1500-2500Kg / h; the dispersed material is classified, and the feeding frequency during classification is 3-16Hz, the fan frequency is 20-60Hz, and the classification efficiency is 200-600Kg / h. It uses a rod pin grinder and dispersion + classification process to treat the artificial graphite oversize, which has a simple process, convenient operation, little damage to the external structure of the material, a high oversize yield, and a high product qualification rate. The qualified oversize is used as a negative electrode material for lithium batteries, showing excellent electrochemical properties, and the first capacity can reach 363.6mAh / g.

[0004] However, the utilization efficiency of the secondary screen material obtained from the existing artificial graphite processing is low, and there is an urgent need for a processing method for processing the secondary screen material into an artificial graphite negative electrode material that can be normally used. Summary of the invention

[0005] The technical problem solved by the present invention is to overcome the low utilization efficiency of the secondary screen material after the existing artificial graphite processing, thereby providing a new processing method for processing the secondary screen material into an artificial graphite negative electrode material that can be normally used. The processing method further mixes the broken and classified materials with the artificial graphite semi-finished products produced normally, and then graphitizes and carbonizes them at high temperature, thereby improving the electrochemical properties of the material, such as specific surface area, tap density and powder compaction density.

[0006] The present invention provides the following technical solutions to solve the above problems.

[0007] The present invention provides a method for treating artificial graphite secondary screen material, which comprises the following steps:

[0008] (1) The artificial graphite secondary sieve material is successively subjected to a disintegration treatment and a classification treatment to obtain material A;

[0009] (2) Material A is mixed with the semi-finished artificial graphite and subjected to graphitization treatment to obtain material B;

[0010] (3) Material B is mixed with modified asphalt and subjected to carbonization treatment to obtain material C;

[0011] (4) The material C is processed into a finished product to obtain a processed artificial graphite negative electrode material.

[0012] In the present invention, the artificial graphite may be conventional artificial graphite in the art, preferably one or more of asphalt coke, petroleum coke and coal-based coke, such as petroleum coke.

[0013] In the present invention, the artificial graphite secondary screen material refers to the material that fails to pass through the screen hole after the artificial graphite is screened twice, which can be prepared by conventional methods in the art, preferably, by the following method:

[0014] (a) crushing the artificial graphite raw material to obtain powder a;

[0015] (b) shaping the powder a to obtain powder b;

[0016] (c) mixing powder b with asphalt and granulating the mixture to obtain powder c;

[0017] (d) graphitizing powder c to obtain powder d;

[0018] (e) mixing powder d with modified asphalt and performing carbonization treatment to obtain powder e;

[0019] (f) Processing the powder e into finished products to obtain artificial graphite secondary screen material.

[0020] In the present invention, the operations and conditions of the pulverization, shaping, granulation, graphitization, carbonization and finished product processing can all be conventional operations and conditions in the art, and the following conditions are particularly preferred in the present invention.

[0021] In step (a), the particle size of the powder a is preferably not greater than 100 μm.

[0022] In step (a), before the pulverization treatment, the raw material is preferably crushed by a jaw crusher.

[0023] Among them, the particle size of the raw material after jaw crushing is preferably not more than 10mm.

[0024] In step (b), the particle size of the powder b is 6-8 μm.

[0025] In step (b), before the shaping process, the powder a is subjected to a classification process, wherein the purpose of the classification process is to remove particles with too large and too small particle sizes in the powder a, so that the particle size is controlled within 6-8 μm.

[0026] In step (b), the shaping is performed twice.

[0027] In step (c), the granulation treatment can be carried out in a conventional granulation equipment in the art, and the granulation equipment is preferably a reactor.

[0028] In step (c), the asphalt may be common asphalt commonly used in the art, preferably asphalt purchased from Sinopec.

[0029] In step (c), the particle size D50 of the asphalt is preferably 3.3-5.5 μm, for example 3.71 μm.

[0030] In step (c), the coking value of the asphalt is preferably 60-75%, such as 67%.

[0031] In step (c), the amount of asphalt used is preferably 18% of the total mass of the powder b and the asphalt.

[0032] In step (d), the graphitization treatment can be carried out in a conventional reaction container in the art, and the reaction container is preferably a box furnace.

[0033] In step (d), the temperature of the graphitization treatment is 2800-3000°C, for example, 3000°C.

[0034] In step (e), the carbonization treatment can be carried out in a conventional reaction container in the art, and the reaction container is preferably a kiln.

[0035] In step (e), the temperature of the carbonization treatment is 1000-1200°C, for example, 1200°C.

[0036] In step (e), the modified asphalt can be common modified asphalt on the market (purchased from Sinopec).

[0037] In step (e), the particle size of the modified asphalt is preferably 3-6 μm, such as 4 μm.

[0038] In step (e), the coking value of the modified asphalt is preferably not higher than 30%, for example 30%.

[0039] In step (e), the density of the modified asphalt at 30°C is preferably 1.05-1.1 g / cm3 , for example 1.07 g / cm 3 .

[0040] In step (e), the amount of modified asphalt is 10%-30% of the total mass of the powder d and the modified asphalt, for example, 15%.

[0041] In step (e), the powder d is preferably mixed with the modified asphalt until they are uniform.

[0042] The uniformly mixed powder d and modified asphalt were stirred at room temperature for 1 hour.

[0043] In step (f), the finished product processing includes the steps of screening and demagnetizing the powder e.

[0044] The screening can be carried out in a conventional screening device in the art, and the screening device is preferably an air flow screen.

[0045] Wherein, the particle size of the air flow screen is preferably 270 mesh.

[0046] Wherein, the screening is preferably performed twice.

[0047] The demagnetization can be performed in a conventional demagnetization machine in the art.

[0048] The demagnetization is preferably performed twice.

[0049] In step (1), the disintegration process can be carried out in a conventional disintegrator in the art.

[0050] Wherein, the host frequency of the disintegrating machine is 20-40 Hz, for example, 30 Hz.

[0051] Wherein, the rotation speed of the disintegrator is 300-1200 r / min, for example, 600 r / min.

[0052] Wherein, the feeding frequency of the dispersing machine is 5-10 Hz, for example, 10 Hz.

[0053] The dispersing efficiency of the dispersing machine is 300-1500 Kg / h, for example 750 Kg / h.

[0054] In step (1), the classification process can be carried out in a conventional classifier in the art.

[0055] Wherein, the feeding frequency of the classifier is 3-10 Hz, for example 8 Hz.

[0056] Wherein, the fan frequency of the classifier is 20-50 Hz, for example, 25 Hz.

[0057] Wherein, the classification efficiency of the classifier is 150-500Kg / h, for example, 200Kg / h.

[0058] In step (1), the particle size D50 of the material A is 11.5-14.5 μm, for example, 13 μm.

[0059] In step (2), the temperature of the graphitization treatment is 2800-3000°C, for example, 3000°C.

[0060] In step (2), the amount of the artificial graphite semi-finished product is 10%-30%, for example, 15%, of the total mass of material A and the artificial graphite semi-finished product.

[0061] The artificial graphite semi-finished product is prepared by sequentially carrying out the above steps (a) to (d).

[0062] In step (3), the amount of modified asphalt used is 10%-30% of the total mass of material B and modified asphalt, for example, 15%.

[0063] In step (3), the temperature of the carbonization treatment is 1000-1200°C, for example, 1200°C.

[0064] In step (3), material B is preferably mixed with the modified asphalt until they are uniform.

[0065] The modified asphalt may be common modified asphalt on the market (purchased from Sinopec).

[0066] Wherein, the particle size of the modified asphalt is preferably 3-6 μm, such as 4 μm.

[0067] Wherein, the coking value of the modified asphalt is preferably not higher than 30%, for example 30%.

[0068] The density of the modified asphalt at 30°C is preferably 1.05-1.1 g / cm 3 , for example 1.07 g / cm 3 .

[0069] Among them, it is preferred to stir the uniformly mixed material B and modified asphalt at room temperature for 1 hour.

[0070] In step (4), the finished product processing includes the steps of screening and demagnetizing material C.

[0071] The screening can be carried out in a conventional screening device in the art, and the screening device is preferably an air flow screen.

[0072] Wherein, the particle size of the air flow screen is preferably 270 mesh.

[0073] Wherein, the screening is preferably performed twice.

[0074] The demagnetization can be performed in a conventional demagnetization machine in the art.

[0075] The demagnetization is preferably performed twice.

[0076] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0077] The reagents and raw materials used in the present invention are commercially available.

[0078] The positive and progressive effects of the present invention are:

[0079] The secondary oversize is processed into an artificial graphite negative electrode material that can be normally used by a new treatment method. Especially when the secondary oversize comes from some products with high capacity requirements, it can increase the capacity of the artificial graphite mixed with it. In addition, the method is simple to operate and easy to implement, and can be used for industrial production. The experimental results show that the artificial graphite negative electrode material obtained after treatment by the method of the present invention has qualified performance, and the useless secondary oversize is effectively utilized. BRIEF DESCRIPTION OF THE DRAWINGS

[0080] Figure 1 This is a scanning electron microscope image of the artificial graphite secondary sieve in Comparative Example 2;

[0081] Figure 2 This is a scanning electron microscope image of the finished product after the secondary screen material in Example 1 is processed. DETAILED DESCRIPTION

[0082] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0083] The artificial graphite produced from the secondary screen material in the embodiment and the artificial graphite obtained by mixing and processing together are the same artificial graphite negative electrode material. The finished artificial graphite is characterized by a particle size D50 of 13.5-15.5 μm and a discharge capacity of 356 mAh / g.

[0084] Example 1

[0085] (1) Dispersion and classification: The secondary screened material is dispersed by a disperser, wherein the disperser frequency is 30 Hz, the rotation speed is 600 r / min, the feed frequency is 10 Hz, and the dispersion efficiency is 750 kg / h; the dispersed material is classified, and the feed frequency during classification is 8 Hz, the fan frequency is 25 Hz, and the classification efficiency is 200 kg / h. The particle size D50 of the obtained material A is 13 μm;

[0086] The preparation steps of the secondary screen material are as follows:

[0087] (a) Crushing treatment: The petroleum coke is crushed by a jaw crusher and then crushed by a mechanical mill to obtain powder a; wherein the particle size after crushing is not greater than 10 mm; and the particle size after crushing is not greater than 100 μm.

[0088] (b) Shaping treatment: powder a is classified once according to the particle size and then shaped twice to obtain powder b, wherein the particle size D50 of powder b is 6-8μm, and the qualified particle size ratio is >99%;

[0089] (c) Granulation: Powder b and asphalt are mixed evenly, and granulated in a reactor to obtain powder c, in which the asphalt ratio is 18%; wherein the asphalt is ordinary asphalt (purchased from Sinopec), with a D50 of 3.71 μm and a coking value of 67%.

[0090] (d) Graphitization treatment: Powder c is graphitized in a box furnace at 3000°C to obtain powder d;

[0091] (e) Carbonization treatment: Powder d and modified asphalt were mixed evenly and stirred for 1 hour before entering the kiln, and then carbonized at 1200°C to obtain powder e. The amount of modified asphalt used was 15% of the total mass of powder d and modified asphalt;

[0092] (f) Finished product processing: The carbonized powder e is screened and demagnetized twice to obtain a secondary screen material.

[0093] (2) Graphitization treatment: The material A after being broken up and classified is mixed with the artificial graphite semi-finished product produced normally and graphitized in a box furnace at 3000°C to obtain material B; the amount of the artificial graphite semi-finished product is 15% of the total mass of the material A and the artificial graphite semi-finished product;

[0094] The normally produced artificial graphite semi-finished product is prepared by sequentially carrying out the above steps (a) to (d).

[0095] (3) Carbonization treatment: Material B and modified asphalt were mixed evenly and stirred at room temperature for 1 hour before entering the kiln, and then carbonized at 1200°C to obtain material C, wherein the amount of modified asphalt was 15% of the total mass of material B and modified asphalt. The modified asphalt was a common modified asphalt on the market (purchased from Sinopec), with a particle size D50 of 4 μm, a coking value of 30%, and a density of 1.07 g / cm at 30°C. 3 .

[0096] (4) Finished product processing: The carbonized material C is screened and demagnetized twice using a 270-mesh air sieve to obtain an artificial graphite negative electrode material with normal performance, such as Figure 2As shown, it is a scanning electron microscope image of the obtained artificial graphite negative electrode material.

[0097] Comparative Example 1

[0098] (1) Dispersing and grading: The secondary screened material obtained in the above steps (a) to (f) is dispersed by a disperser, wherein the frequency of the disperser is 30 Hz, the rotation speed is 600 r / min, the feed frequency is 10 Hz, and the dispersing efficiency is 750 kg / h; the dispersed material is graded, the feed frequency during grading is 8 Hz, the fan frequency is 25 Hz, the grading efficiency is 200 kg / h, and the obtained material particle size D50 is 13 μm.

[0099] (2) Finished product processing: The dispersed material is directly screened twice and demagnetized twice using an air flow screen with a particle size of 270 meshes to obtain an artificial graphite negative electrode material with normal performance.

[0100] Comparative Example 2

[0101] According to the preparation steps (a) to (f) of the secondary oversize material in Example 1 above, a secondary oversize material is obtained, such as Figure 1 As shown, it is a scanning electron microscope image of the obtained secondary sieve material.

[0102] Comparative Example 3

[0103] First, prepare the powder e according to the steps (a) to (e) of the secondary screen material in the above embodiment 1, and then screen and demagnetize the carbonized powder e twice to obtain an artificial graphite negative electrode material without secondary screen material.

[0104] Effect Example 1 Morphology Characterization

[0105] Scanning electron microscope (SEM) test: Instrument model: S-4800, Hitachi, Japan.

[0106] The morphology of the secondary oversize materials in Example 1 and Comparative Example 2 was characterized by SEM.

[0107] Figure 1 This is a 2000x SEM image of the untreated secondary sieve material of Comparative Example 2. Figure 2 This is a 2000-fold SEM image of the secondary sieve material after treatment in Example 1. Figure 2 Example 1 compared to Figure 1 In Comparative Example 2, the structure of the finished artificial graphite product obtained by processing the secondary screen material and the artificial graphite semi-finished product together becomes loose, there are no whole large particles, and the uniformity and safety of the material are improved to a certain extent.

[0108] Effect Example 2

[0109] The electrochemical performance of the artificial graphite negative electrode materials of the above Example 1 and Comparative Examples 1-3 was tested respectively, and the test results are listed in the following Table 1, wherein the discharge capacity is measured as follows: Use the Blue Electric Test Cabinet to perform charge and discharge tests on the button to obtain the discharge capacity of the negative electrode material, wherein the button radius is 10mm, the thickness is 3.2mm, and the button model is CR2032. The charge and discharge system is as follows: first, discharge to 5mV at a constant current of 0.05C, let stand for 10min, then charge to 2.0V voltage at a constant current of 0.1C, and let stand for 5min. And the measurement of the tap density uses the Zhuhai OMEK TD-03 model, 3000 times; the measurement of the compacted density uses the Ruikewei FT-100F powder automatic compaction density meter, and the powder pressure is 5T; the measurement of the specific surface area uses the Best BSD-660S, and the default general automatic test parameters are used.

[0110] Table 1:

[0111]

[0112] Conclusion: Comparative Example 1 is the secondary screen material obtained by only breaking up and grading, but without graphitization and carbonization treatment steps, Comparative Example 2 is the secondary screen material screened from the normal artificial graphite finished product, Comparative Example 3 is the normal artificial graphite finished product, and Example 1 is the artificial graphite finished product obtained by processing the secondary screen material and the artificial graphite semi-finished product together. It can be seen from the table that the performance of Example 1 is close to that of Comparative Example 3, and it is a qualified artificial graphite negative electrode material. Although the particle size of Comparative Example 1 is close to that of normal artificial graphite, there is still a significant gap in specific surface, vibration and powder pressure, so it cannot be used as a battery negative electrode material.

[0113] In summary, the secondary screen material can be treated by the method of the present invention to obtain an artificial graphite negative electrode material with performance that meets the requirements and has qualified performance.

Claims

1. A method for treating artificial graphite secondary screen material, characterized in that: It includes the following steps: (1) The artificial graphite secondary sieve material is successively subjected to a disintegration treatment and a classification treatment to obtain material A; (2) Material A is mixed with the semi-finished artificial graphite and subjected to graphitization treatment to obtain material B; (3) Material B is mixed with modified asphalt and subjected to carbonization treatment to obtain material C; (4) The material C is processed into a finished product to obtain a processed artificial graphite negative electrode material.

2. The method for processing artificial graphite secondary oversize according to claim 1, characterized in that: The artificial graphite secondary screen material is prepared by the following method: (a) crushing the artificial graphite raw material to obtain powder a; (b) shaping the powder a to obtain powder b; (c) mixing powder b with asphalt and granulating the mixture to obtain powder c; (d) graphitizing powder c to obtain powder d; (e) mixing powder d with modified asphalt and performing carbonization treatment to obtain powder e; (f) Processing the powder e into finished products to obtain artificial graphite secondary screen material.

3. The method for processing artificial graphite secondary oversize according to claim 1, characterized in that: The artificial graphite semi-finished product is prepared by the following method: (a) crushing the artificial graphite raw material to obtain powder a; (b) shaping the powder a to obtain powder b; (c) mixing powder b with asphalt and granulating the mixture to obtain powder c; (d) Graphitizing powder c to obtain powder d, which is the artificial graphite semi-finished product.

4. The method for processing artificial graphite secondary oversize according to claim 1, characterized in that: It meets one or more of the following conditions: (1) The artificial graphite is one or more of pitch coke, petroleum coke and coal-based coke, such as petroleum coke; (2) In step (1), the particle size D50 of the material A is 11.5-14.5 μm, for example, 13 μm; (3) In step (2), the amount of the artificial graphite semi-finished product is 10%-30% of the total mass of the material A and the artificial graphite semi-finished product, for example, 15%; (4) In step (3), the amount of modified asphalt is 10%-30% of the total mass of material B and modified asphalt, for example, 15%; (5) In step (3), the particle size of the modified asphalt is 3-6 μm, for example, 4 μm; (6) In step (3), the coking value of the modified asphalt is not higher than 30%, for example, 30%; (7) In step (3), the density of the modified asphalt at 30°C is 1.05-1.1 g / cm 3 , for example 1.07 g / cm 3 .

5. The method for processing artificial graphite secondary oversize according to claim 1, characterized in that: It meets one or more of the following conditions: (1) In step (1), the dispersing process is carried out in a dispersing machine; wherein the main engine frequency of the dispersing machine is 20-40 Hz, for example, 30 Hz; the rotation speed of the dispersing machine is 300-1200 r / min, for example, 600 r / min; the feeding frequency of the dispersing machine is 5-10 Hz, for example, 10 Hz; the dispersing efficiency of the dispersing machine is 300-1500 Kg / h, for example, 750 Kg / h; (2) In step (1), the classification process is carried out in a classifier; wherein the feed frequency of the classifier is 3-10 Hz, for example, 8 Hz; the fan frequency of the classifier is 20-50 Hz, for example, 25 Hz; the classification efficiency of the classifier is 150-500 kg / h, for example, 200 kg / h; (3) In step (2), the temperature of the graphitization treatment is 2800-3000°C, for example, 3000°C; (4) In step (3), the temperature of the carbonization treatment is 1000-1200° C., for example, 1200° C.; (5) In step (3), material B is mixed with modified asphalt until they are uniform; (6) In step (4), the finished product processing includes the steps of screening and demagnetizing material C.

6. The method for processing artificial graphite secondary oversize according to claim 5, characterized in that: It meets one or more of the following conditions: (1) In step (3), the uniformly mixed material B and modified asphalt are stirred at room temperature for 1 hour; (2) The screening is performed in a screening device, and the screening device is an airflow screen; wherein the particle size of the airflow screen is 270 mesh; (3) The screening is performed twice; (4) The demagnetization is carried out in a demagnetizer; (5) The demagnetization is performed twice.

7. The method for processing artificial graphite secondary oversize according to claim 2 or 3, characterized in that: It meets one or more of the following conditions: (1) In step (a), the particle size of the powder a is not greater than 100 μm; (2) In step (b), the particle size of the powder b is 6-8 μm; (3) In step (c), the amount of asphalt used is 18% of the total mass of powder b and asphalt; (4) In step (c), the particle size D50 of the asphalt is 3.3-5.5 μm, for example 3.71 μm; (5) In step (c), the coking value of the asphalt is 60-75%, for example 67%.

8. The method for processing artificial graphite secondary oversize according to claim 2 or 3, characterized in that: It meets one or more of the following conditions: (1) In step (a), before the pulverizing process, the raw material is crushed by a jaw crusher, wherein the particle size of the raw material after the jaw crushing is not more than 10 mm; (2) In step (b), before the shaping process, the powder a is subjected to a classification process; (3) In step (b), the shaping is performed twice; (4) In step (c), the granulation process is carried out in a granulation device, and the granulation device is a reactor; (5) In step (d), the graphitization treatment is carried out in a reaction container, and the reaction container is a box-type furnace; (6) In step (d), the temperature of the graphitization treatment is 2800-3000°C, for example, 3000°C.

9. The method for processing artificial graphite secondary oversize according to claim 8, characterized in that: It meets one or more of the following conditions: (1) Stir the uniformly mixed powder d and modified asphalt at room temperature for 1 h; (2) The screening is performed in a screening device, and the screening device is an airflow screen; wherein the particle size of the airflow screen is 270 mesh; (3) The screening is performed twice; (4) The demagnetization is carried out in a demagnetizer; (5) The demagnetization is performed twice.

10. The method for processing artificial graphite secondary oversize according to claim 2, characterized in that: It meets one or more of the following conditions: (1) In step (e), the particle size of the modified asphalt is 3-6 μm, for example, 4 μm; (2) In step (e), the coking value of the modified asphalt is not higher than 30%, for example, 30%; (3) In step (e), the density of the modified asphalt at 30°C is 1.05-1.1 g / cm 3 , for example 1.07 g / cm 3 ; (4) In step (e), the amount of modified asphalt is 10%-30% of the total mass of powder d and modified asphalt, for example, 15%; (5) In step (e), the carbonization treatment is carried out in a reaction vessel, and the reaction vessel is a kiln; (6) In step (e), the temperature of the carbonization treatment is 1000-1200° C., for example, 1200° C.; (7) In step (e), the powder d is mixed with the modified asphalt until they are uniform; (8) In step (f), the finished product processing includes the steps of screening and demagnetizing the powder e.

Citation Information

Patent Citations

  • Production method for modified artificial graphite negative electrode material

    CN105428615A

  • Low-cost composite graphite negative electrode material and preparation method thereof

    CN112479198A

  • Artificial graphite composite negative electrode material for lithium ion battery as well as preparation method and application of artificial graphite composite negative electrode material

    CN114597361A

  • Processing method of artificial graphite oversize product

    CN115814921A

  • Fast-charging graphite negative electrode material as well as preparation method and application thereof

    CN116161656A

Cited By

  • Processing method of artificial graphite sieve loading material

    CN120243225A